1976
DOI: 10.1103/physreva.13.74
|View full text |Cite
|
Sign up to set email alerts
|

Ionization, charge exchange, and excitation in F + Ar and F + Kr collisions

Abstract: We have measured projectile and target x-ray cross sections for F+ Ar and F+ Kr collisions using fluorine beams of charge states 7+, 8+, and 9+ with energies from 20 to 76 MeV. Pronounced enhancements for the Ar K and Kr L vacancy cross sections using F + ions compared to those for the 7+ projectile can be explained by charge exchange as described by an empirically scaled Brinkman-Kramers theory. The Ar L, Kr K, and Kr M cross sections are found to exhibit features expected for Coulomb ionization. The projecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This value is in excellent agreement with a measurement by Winters et al [19] of 4,100 b. 'Cross sections of Ar and Kr measured by Hopkins et al [24] at overlapping energies are not directly comparable since these measurements were done with higher (q> 7 § charge states and therefore significant deviations are to be expected [19,23]. For 19 MeV F 5+ Tawara et al [25] measured a Si K Xray cross section of (1.63_+0.16).…”
Section: A K-shell Ionisation Of the Target Atomsupporting
confidence: 89%
See 2 more Smart Citations
“…This value is in excellent agreement with a measurement by Winters et al [19] of 4,100 b. 'Cross sections of Ar and Kr measured by Hopkins et al [24] at overlapping energies are not directly comparable since these measurements were done with higher (q> 7 § charge states and therefore significant deviations are to be expected [19,23]. For 19 MeV F 5+ Tawara et al [25] measured a Si K Xray cross section of (1.63_+0.16).…”
Section: A K-shell Ionisation Of the Target Atomsupporting
confidence: 89%
“…The dependence of the X-ray cross sections on the projectile energy is quite satisfactorily reproduced by the BEA calculations, indicating the dominance of direct ionization as vacancy production mechanism. This ionization process seems also to prevail at still higher energies for ion charge states __>7 § [24]. Especially at low projectile velocities, ionization of the Kr L-shell by electron promotion from orbitals connected with the projectile K-shell (3da orbital for example) and the target atom L-shells could be important.…”
Section: B L-and M-shell Ionization Of Target Atomsmentioning
confidence: 94%
See 1 more Smart Citation
“…The cross section values measured using the two detectors agreed with one another to within 5-10% at all the measured energies and charge states of the incident projectile. For absolute normalization, the Ar K x-ray yields were measured, in the same geometry, using 56 and 77 MeV F ion beams in different charge states for which the x-ray cross sections are known (Hopkins et al 1974). It was found that the cross sections derived from the present measurements were slightly lower (by a factor of 1.3) than those obtained by Hopkins et al However, we have used the existing data of Hopkins et al (1974) to normalize our cross section data.…”
Section: Data Analysis Results and Discussionmentioning
confidence: 99%
“…The strong effects of projectile charge state on inner-shell ionization [1][2][3][4] have been reported by a number of groups for gas targets.…”
Section: Introductionmentioning
confidence: 84%